Optimizing ultra high-performance concrete (UHPC) mix proportions using technique for order preference by similarity to ideal solution (TOPSIS) for enhanced performance: Precision towards optimal concrete engineering - Sathya Sai Regalla; N. Senthil Kumar (Case Studies in Construction Materials)
Ultra-High-Performance Concrete (UHPC) mix design poses a longstanding challenge for concrete engineers, as it involves optimizing multiple interdependent parameters to achieve desired performance characteristics. Since the early 1990s, researchers globally have explored various approaches to refine the selection of optimal UHPC compositions, addressing criteria such as strength, durability, workability, cost analysis, environmental impact, and microstructural properties. In this study, we utilize the Technique for Order Preference by Similarity to an Ideal Solution (TOPSIS) as a Multi-Criteria Decision-Making (MCDM) tool to navigate the complexities of UHPC mix selection. TOPSIS offers a structured and objective framework for ranking UHPC mix alternatives by synthesizing diverse performance indicators into a single, unified score. This enables decision-makers to systematically evaluate and prioritize mix designs based on their proximity to an ''ideal'' solution that maximizes beneficial factors while minimizing unfavorable ones. By employing TOPSIS, our methodology not only streamlines the comparison process among competing UHPC mixes but also enhances precision in decision-making. This approach supports concrete engineers in selecting UHPC formulations aligned with specific performance requirements, leading to more efficient and effective applications in practice. In essence, TOPSIS transforms a complex, multi-faceted decision landscape into a more accessible, data-driven process, promoting optimized UHPC design for advanced structural performance. Optimization in this context refers to identifying a mix design that provides superior performance within defined constraints, balancing essential factors and minimizing extraneous impacts. By integrating TOPSIS with these selection criteria, in this research contributes to more strategic, comprehensive, and scientifically grounded UHPC mix design, fostering advancements in concrete engineering.